Hubungan penyakit periodontal dengan covid-19 - Suwandi, Trijani; Carissa Nurhasinah Wiriawan, Deandra (Jurnal Kedokteran Gigi Terpadu, 2024)
Periodontitis is a chronic, multifactorial, inflammatory disease, associated with plaque biofilms and characterized by the progressive destruction of the tooth-supporting structures. Periodontal diseases can increase the inflammatory response in patients, which might exacerbate the systemic symptoms and clinical course of coronavirus (COVID-19). The potential association of periodontitis and COVID-19 severity can be explained by the alteration in the expression of cellular receptors enhancing the virulence of SARS-CoV-2 and by periodontal pockets acting as viral reservoirs. These associations between periodontitis and COVID could be due to the fact that both diseases share common immune pathways such as the NF-κB pathway, NLRP3/IL-1β pathway, and IL-6 signaling pathway as well as common risk factors such as gender, lifestyle, and comorbidities. This suggests that the two diseases may be linked through the same genetic pathway.